INVESTIGATION OF POTENTIALITIES TO SET AUTOMATICALLY AMPLITUDE VALUES OF MAGNETIC INDUCTION WHILE MEASURING MAGNETIC CHARACTERISTICS OF ELECTRICAL-SHEET STEEL - I. I. Branovitsky; M. N. Putyrsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The problems relating to an automation of measurement of magnetic characteristics of electrical-sheet steel have been considered in the paper. The paper investigates efficiency of an application of some well-known iterative methods for setting the required amplitude value of a magnetic induction of the material to be tested. It is shown that the most efficient method providing a fast and stable convergence of an iterative process while testing either textured or isotropic electrical-sheet steel is a parabola method.